Performance Evaluation of Modified Bitumen with Replaced Percentage of Waste Cooking Oil & Tire Rubber with Bagasse Ash as Modifier - Junaid Khan; Arshad Hussain; Fazal Haq; Kamran Ahmad; Kamran Mushtaq (Civil Engineering Journal, 2019)
Flexible pavements are the major type of pavement use in recent days. Bitumen is the main constituent’s part of flexible pavement. Bitumen is the by-produce of petroleum. The depleting reserve of petroleum led researcher to look for alternative binder. This research work explicitly aim at replacing certain percentage of bitumen with Tire Rubber powder (TR), Waste Cooking Oil (WCO) in the presence of Bagasse Ash (BA) as a modifier. Physical test were performed to determine optimum percentages of TR, WCO and BA that can be used as a percentage replacement in bitumen. Result shows that up to 20 % of bitumen can be successfully replaced without affecting performance of bitumen. Performance Tests such as Dynamic Shear Rheometer, Rotatory thin film oven, Pressure aging Vessel and Bending Beam Rheometer were performed on modified samples for its physical and rheological properties. Modified bitumen showed good resistance against rutting, skidding and low temperature cracking. The research work directly contribute in developments of alternative binder for flexible pavement which is a leading research trend these days and environmental friendly initiative.